2011
DOI: 10.1007/s10661-011-1919-8
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine residues in blood of cinereous vultures and Eurasian griffon vultures in a northeastern Mediterranean area of nature conservation

Abstract: In the National Park of Dadia-Lefkimi-Soufli Forest (Dadia NP, Greece), seven "target" PCBs and 16 organochlorine pesticides (OCs) were analysed in blood samples of cinereous vultures (Aegypius monachus) and Eurasian griffon vultures (Gyps fulvus). PCB congeners 138, 153 and 180 predominated in both species' blood samples. In both species, no differences were detected in congener levels between successive age classes, but in cinereous vulture, there were significant differences between adult and nestling in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
3
13
1
Order By: Relevance
“…The studies in India found p,p 0 -DDE in GV to be 16.2 ng/ml in plasma (maximum value 26.5), in whiterumped vultures to be 16.3 ng/ml (maximum value 39.5), in Egyptian vultures to be 8.8 ng/ml (maximum value 25.6), and in black kites to be 15.3 ng/ml (maximum value 137) . Whole blood levels of p,p 0 -DDE in GV and cinereous vultures in Greece were 4.49 and 3.80 ng/g, respectively (maximum values 10.59 and 9.42 ng/g, respectively) (Goutner et al 2011). In the nestlings of African vultures, the two specimens of cape griffon vultures examined had concentrations of 12.8 and 29.9 ng/ml in whole blood, with lower levels in the other two vulture species (van Wyk et al 2001).…”
Section: As and CDmentioning
confidence: 88%
See 3 more Smart Citations
“…The studies in India found p,p 0 -DDE in GV to be 16.2 ng/ml in plasma (maximum value 26.5), in whiterumped vultures to be 16.3 ng/ml (maximum value 39.5), in Egyptian vultures to be 8.8 ng/ml (maximum value 25.6), and in black kites to be 15.3 ng/ml (maximum value 137) . Whole blood levels of p,p 0 -DDE in GV and cinereous vultures in Greece were 4.49 and 3.80 ng/g, respectively (maximum values 10.59 and 9.42 ng/g, respectively) (Goutner et al 2011). In the nestlings of African vultures, the two specimens of cape griffon vultures examined had concentrations of 12.8 and 29.9 ng/ml in whole blood, with lower levels in the other two vulture species (van Wyk et al 2001).…”
Section: As and CDmentioning
confidence: 88%
“…Levels of PCB 153 in GV and cinereous vultures in Greece were 4.00 and 3.42 ng/g, respectively (Goutner et al 2011). Egyptian vultures in Spain showed levels ranging from means of 0.54-4.1 ng/ml in serum (maximum value 20) (Gomara et al 2004).…”
Section: Pcb 153 Congenermentioning
confidence: 95%
See 2 more Smart Citations
“…These facts led us to suggest that latent factors, which are not yet clear, may be influencing the decline. Exposure to environmental contaminants that have an endocrine disrupting effect may be a path worth exploring (Younes 1999, Vos et al 2000, Fisher et al 2006, Frederick and Jayasena 2010, Goutner et al 2011). One of the first studies conducted in Israel regarding possible contamination exposure has reported low levels of heavy metals in griffons' blood (Shlosberg et al 2012).…”
Section: Discussionmentioning
confidence: 99%